2022
DOI: 10.1080/20002297.2022.2047491
|View full text |Cite
|
Sign up to set email alerts
|

Lack of direct association between oral mucosal lesions and SARS-CoV- 2 in a cohort of patients hospitalised with COVID-19

Abstract: Background COVID-19 is a disease affecting various human organs and systems, in which the virus seeks to interact with angiotensin-converting enzyme 2 receptors. These receptors are present in the oral cavity, but the direct relationship between such an interaction and possible oral manifestations of COVID-19 is still unclear. Aim The present study evaluated oral manifestations in a cohort of COVID-19 patients during the period of hospitalisation. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 36 publications
(49 reference statements)
2
11
0
2
Order By: Relevance
“…Therefore, intubation in the course of treatment may be associated with the occurrence of traumatic ulcers, thus explaining their high prevalence in severe COVID-19 cases. Interestingly, in line with our findings, a recent study ( 69 ) also demonstrated a possible association between the intubation process in COVID-19 patients and traumatic ulcers. The cohort study analyzed COVID-19 patients with oral mucosal changes associated with hospitalization and found a statistical association between intubation and oral lesions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, intubation in the course of treatment may be associated with the occurrence of traumatic ulcers, thus explaining their high prevalence in severe COVID-19 cases. Interestingly, in line with our findings, a recent study ( 69 ) also demonstrated a possible association between the intubation process in COVID-19 patients and traumatic ulcers. The cohort study analyzed COVID-19 patients with oral mucosal changes associated with hospitalization and found a statistical association between intubation and oral lesions.…”
Section: Discussionsupporting
confidence: 93%
“…Some proposed that oral mucosal lesions may act as a secondary manifestation of COVID-19 ( 6 , 10 , 12 , 17 ), or that COVID-19 disrupts the local microbiome or impairs oral mucosal immunity, causing oral mucosal lesions ( 12 , 27 , 72 ). Others pointed out that it may be caused by poor oral hygiene practice or intubation process during hospitalization, or adverse effects of COVID-19 medication ( 15 , 69 ). However, similar to the findings of this systemic review, most of them ( 3 , 5 , 16 , 20 , 21 , 23 , 24 ) still cannot conclude that COVID-19 has an association with oral mucosal lesions due to the lack of detailed reports.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the floor of mouth lesion (Figure 3b) was composed of asymptomatic reddish petechiae. We do not believe that oral mucosal lesions are directly associated with SARS-CoV-2 25 . However, previous studies 26,27 have shown vascular involvement and detection of the SARS-CoV-2 spike protein in inflammatory endothelial cells and keratinocytes, as well as in acinar and ductal cells of the minor salivary glands.…”
Section: Patient Amentioning
confidence: 82%
“…Italy accounted for the most articles, with 14 studies [ 16 , 19 , 20 , 22 , 23 , 28 , 29 , 36 , 37 , 58 , 66 , 72 , 81 , 86 ]. This was followed by India with 8 studies [ 17 , 33 , 44 , 45 , 50 , 55 , 80 , 83 ], United States with 7 studies [ 21 , 25 ,, 30 , 31 , 54 , 62 , 79 ], Brazil with 7 studies [ 9 , 47 , 49 , 52 , 56 , 75 , 77 ], and both Egypt and Turkey with 5 studies each [ 34 , 38 , 41 , 68 , 71 ] and [ 26 , 39 , 42 , 48 , 64 ], respectively. Iran [ 5 , 53 , 59 , 60 ], Iraq [ 12 , 43 , ...…”
Section: Resultsmentioning
confidence: 99%
“…We further subdivided the taste disorders into additional categories. These include complete loss of taste, or ageusia, as reported in 22 studies [ 12 , 14 , 20 , 23 , 35 , 40 − 42 , 44 , 49 , 53 , 55 , 56 , 58 , 63 , 65 , 67 , 70 , 72 , 74 , 85 ], taste alteration or dysfunction, as reported in 19 studies [ 5 , 13 , 16 19 , 21 , 22 , 29 , 36 , 38 , 46 , 51 , 54 , 66 , 78 , 84 − 86 ], dysgeusia, as reported in 7 studies [ 24 , 28 , 37 , 50 , 54 , 59 , 60 ], and amblygeustia, as reported in only one study [ 15 ].…”
Section: Resultsmentioning
confidence: 99%